The Influence of Self-Efficacy on Anxiety and Perfectionism among Dancers - Ananya; Smriti Sethi (International Journal of Behavioral Sciences, 2026)
The world of dance, though celebrated for its creativity and artistic freedom, often carries considerable psychological demands on performers. Beyond the physical rigor, dancers navigate pressures of performance standards, audience expectations, and internalized goals of perfection. This study examined how self-efficacy—an individual’s belief in their own capability—shapes the experiences of anxiety and perfectionism among dancers, with a particular focus on gender differences. A balanced sample of 120 dancers (60 males and 60 females) was assessed using standardized psychological scales, and the data were analyzed through t-tests, Pearson correlations, and regression analyses to evaluate both relational and predictive dynamics. Results revealed no significant gender differences in the overall levels of self-efficacy, anxiety, or perfectionism. However, the patterns of relationships among these variables differed by gender. For male dancers, self-efficacy demonstrated a protective quality: it was positively correlated with both excellencism (adaptive perfectionism) and maladaptive perfectionism, while simultaneously showing a negative relationship with anxiety. Regression analyses further confirmed these links, as self-efficacy significantly predicted anxiety (R² = 0.116), excellencism (R² = 0.219), and maladaptive perfectionism (R² = 0.176) among males. In contrast, for female dancers, self-efficacy was positively associated only with excellencism, and regression results confirmed that it predicted this adaptive trait (R² = 0.158), but not anxiety or maladaptive perfectionism. These findings highlight gender-specific nuances in the psychological dynamics of dance. While self-efficacy functions as a buffer against anxiety and maladaptive tendencies in male dancers, its role for females appears more focused on fostering adaptive striving for excellence. Overall, enhancing self-efficacy may be a critical intervention strategy in dance training programs, promoting not only sustained performance and artistic growth but also mental well-being across genders.
Keywords: Anxiety; Dance; Excellencism; Perfectionism; Self-Efficacy